A BIBLIOGRAPHY ON THE APPLICATION OF STATISTICAL METHODS TO ACCOUNTING AND AUDITING. - Trueblood, Robert M.; Monteverde, Robert J. (The Accounting Review, 1954)
This article presents a bibliography on the application of statistical methods to accounting and auditing. Section I includes articles, books and papers which have been published up to November 30, 1953, and which relate specifically to the application of statistical techniques to accounting and auditing problems. Section II includes unpublished papers on the subject of the application of statistical methods to accounting and auditing. Section III lists a number of statistical texts, reference works, and tables which may be helpful to the accountant interested in going deeper into the field of statistical theory or in making specific applications. In section IV this section are listed a limited number of articles and papers which are generally more technical and which relate to specific areas of statistical applications. This bibliography was prepared in connection with a broad study of the application of statistical techniques to accounting and auditing problems being carried in some colleges of the U.S.